ANALISIS DRAMA KETHOPRAK SISWO BUDOYO TULUNGAGUNG SEBAGAI KOLABORASI SENI DRAMA, MUSIK, DAN TARI JAWA - Wijayanto, Wasis; Maulida, Vina Cahya; Khalimah, Umi (Universitas Tanjungpura, 2025)
Kethoprak is a traditional Javanese performing art, as well as a medium for cultural preservation through a combination of drama, music and dance elements.The background to this research is that the existence of kethoprak remains relevant, because the current generation is more interested in digital entertainment. This research aims to examine the collaboration of artistic elements in Kehtoprak Siswo Budoyo Tulungagung and its role in maintaining Javanese culture. The main focus of this research is how art elements are collaborated and their contribution to the preservation of traditions. This research uses a qualitative descriptive approach, data is obtained through literature study methods and staging analysis. The research results show that the combination of art elements creates a distinctive aesthetic that is displayed through symbolism, dialogue and dance movements. This research emphasizes the importance of traditional art as part of a cultural preservation strategy in the modern era, as well as providing inspiration for the sustainable development of local art.